DETERMINAN PEKERJA ANAK DI INDONESIA: DINAMIKA TINGKAT PENDIDIKAN DAN KEMISKINAN - Nada Audrya; Fitriyani Fitriyani; Abd. Jamal; Zulkifli Zulkifli; Riswandi Riswandi (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract This study aims to analyze the factors that affect child labor in 33 provinces in Indonesia. This study uses secondary data from 2010 to 2019. The method used in this study is the panel data regression which examines the effect of poverty and length of the school on child labor. The results showed that poverty had a positive and significant effect on child labor. Meanwhile, the education variable has a negative and significant effect on child labor. Therefore, it is recommended for the government to provide assistance to poor families and also socialize the importance of education as well as create training and skills programs and scholarships for poor students.Keyword: Child Labor, Poverty, Education